Arco de Maguerez como ferramenta no ensino da anatomia humana - Raposo Neto, Luiz Torres (2024)
The teaching of Human Anatomy has long been developed through theoretical presentations, followed by practical lessons and memorization, which are often considered monotonous. In this perspective, different methodological strategies are sought to implement the teaching process, which promotes the student's protagonism. In this scenario, the objective was to analyze the Maguerez Arch as a tool in the teaching of morphofunctional sciences. The research is classified as a field study, with a quantitative approach, carried out in a public institution in Fortaleza-Ceará, with medical students. The students were divided into two groups: traditional teaching and intervention (application of the Maguerez Arch). The ethical precepts, governed by Resolution No. 466/12 of the National Health Council, were prioritized and the project was approved by the CEP, No. 5,589,091. The normality of the data was verified by the Shapiro- Wilk test. The results that followed a parametric distribution were analyzed by Analysis of Variance (ANOVA) followed by Tukey's test as post hoc. Those that did not follow the normal distribution were analyzed by non-parametric statistics using the Kruskal-Wallis test followed by Dunn's. For all analyses, p<0.05 was considered significant. The findings show that both traditional teaching and the Maguerez Arch were efficient for the students' immediate learning, since a statistically significant difference was observed in the pre-test hits when compared to the post-test in the acquisition of short-term knowledge in both groups. Regarding long-term learning, the potential of using the arch was evidenced, since a significant difference was observed in relation to the traditional group. It was found that the methodology of problematizing the Maguerez Arch applied to the teaching of Human Anatomy proved to be significantly effective for students in acquiring cognitive knowledge in the short and, mainly, in the long term, when compared to the traditional group.